MODELLING BATTERY SWAPPING INDUSTRY DEVELOPMENT STRATEGY TO SUPPORT NET ZERO EMISSIONS TRANSITION - Riskiyadi; Setiawan, Andri D. (The South African Journal of Industrial Engineering, 2024)
The Government of Indonesia has set a roadmap towards net zero emissions by 2060, which includes accelerating the adoption of electric motorcycles. The government assigned the State Electricity Company (PLN) to accelerate the adoption by optimizing the potential of conventional motorcycle users and ride hailing. The battery swapping scheme is an attractive choice for companies to increase their profits. However, users still experience uncertainty about battery swapping. It is thus imperative to implement a battery reservation strategy to make it easy for battery swapping users to exchange them. The battery swapping industry is a complex system that involves many interrelated elements. Such a development of strategy would require a holistic view of the process and a definition of the relationships between the elements. This research aimed to develop a conceptual model for a battery swapping industry development strategy with a system dynamic modelling approach and a business model canvas framework. The conceptual model is presented in a system diagram, and a causal loop diagram provides the first information that has an impact on the company’s intervention in the battery swapping industry development strategy. Furthermore, the business model canvas should help to communicate the key aspects easily.